2023
DOI: 10.1093/restud/rdad026
|View full text |Cite
|
Sign up to set email alerts
|

Credit Access, Selection, and Incentives in a Market for Asset-Collateralized Loans: Evidence From Kenya

Abstract: We study the potential for asset collateralization to expand access to credit in rural Kenya. Increasing the share of a loan for a durable agricultural asset that is collateralized by the physical asset itself (from zero to 96%) while reducing the share backed by financial assets increases loan take-up considerably, with only a very limited impact on repayment behavior and the lender’s profitability. A Karlan-Zinman test finds evidence of small and marginally significant selection effects in some specification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In this way, the percieved default rate can be identified from the difference in WTP between SACL and OACL, combined with the difference between WTA and predicted WTA for the endowed item. 31 Table 5 displays the estimation results under different conditions. In addition to reporting parameters we directly estimate, we also report implied parameters (loss aversion λ and projection bias α) in the standard KR model and the implied mean and standard deviation of the item valuation.…”
Section: Identification and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the percieved default rate can be identified from the difference in WTP between SACL and OACL, combined with the difference between WTA and predicted WTA for the endowed item. 31 Table 5 displays the estimation results under different conditions. In addition to reporting parameters we directly estimate, we also report implied parameters (loss aversion λ and projection bias α) in the standard KR model and the implied mean and standard deviation of the item valuation.…”
Section: Identification and Resultsmentioning
confidence: 99%
“…. 31 In terms of the moments observed in the data, the default rate can be expressed as d/(1 − d) = (W T P S − W T P O )/(W T A − W T A), given that three items are valued equally. 32 For the model to be identified, when we exclude one of W T A and W T A, we need to fix the default rate.…”
Section: Identification and Resultsmentioning
confidence: 99%
“…Field et al (2013) is the exception and studies both new and existing borrowers. 1 By showing no evidence of selection effects from introducing flexibility to new clients, we also contribute to the literature assessing the extent of selection in low-income country credit markets (see e.g., Karlan and Zinman 2009;Ahlin et al 2020;Beaman et al 2020;Gertler, Green, and Wolfram 2023;Jack et al 2023).…”
Section: Introductionmentioning
confidence: 94%
“…Specific products may also be offered on credit more formally, with various collateral relationships. For example, water tanks are supplied via self-collateralized loans (Jack et al 2023), and solar lanterns via digitally collateralized loans (Gertler et al 2021). Retailers may also provide consumers with bundled insurance, in the form of warranties or rainfall insurance bundled with hybrid seeds (Bulte et al 2020).…”
Section: Relevant Value Chainsmentioning
confidence: 99%
“…In another instance of supply chain microfinancing, this time in the dairy industry in Kenya, recent work by Jack et al (2023) has shown the promise of self-collateralized asset loans. While selfcollateralized loans are common in developed economies for the acquisition of large assets, including houses, vehicles, and business equipment, they are less common in developing countries.…”
Section: Credit and Equitymentioning
confidence: 99%